Integrating strategies for the treatment of ischemic heart disease based on clinical instrumental and molecular genetic analysis (Multidisciplinary Journal of Science and Technology, 2025)
Recent progress in the comprehension and management of heart diseases, specifically those related to atherosclerosis, is highlighted. The importance of employing genetic insights alongside advancements in biotechnology and pharmacology is underscored to create tailored treatment options for individuals suffering from severe forms of conditions such as Familial Hypercholesterolemia, who do not respond effectively to conventional lipid-lowering interventions.Limitations of current tools used for assessing cardiovascular risk, particularly in secondary prevention settings, are discussed. There is a critical need to enhance understanding of patient variability and the impact of lifestyle and environmental factors on health outcomes. Additionally, how gut microbiota and dietary practices contribute to inflammatory processes associated with atherosclerosis is examined, emphasizing the necessity for a comprehensive approach to understanding disease mechanisms.Furthermore, the analysis elaborates on discoveries from large-scale genetic studies that illuminate the complex genetic landscape of coronary artery issues and the significant influence of specific genetic variations. Integrated approaches across multiple biological layers are advocated to discover functional pathways connected to coronary conditions, while also identifying potential biomarkers relevant to acute myocardial infarction and subsequent heart failure.The relationship between oral health issues, such as gum disease, and cardiovascular problems is explored, with suggestions for using modern statistical methods to establish causality. Lastly, the significance of adopting innovative imaging methods and blood markers is emphasized to enhance diagnostic and prognostic capabilities in relation to coronary artery disease and similar conditions. This synthesis reflects a dynamic shift in research focused on improving prevention, diagnosis, and therapeutic strategies for ischemic heart disease.